Railway condition monitoring using a hybrid multi-view stereopsis and real-time kinematic geolocation pipeline for dense reconstruction - Grabe, P.J. (Hannes) (University of Pretoria, 2022)
Thesis (PhD (Civil Engineering))--University of Pretoria, 2022.